Hubungan antara faktor organisasi dengan prestasi sistem maklumat perakaunan - Kamarulbaraini Keliwon; Aini Aman; Azmi Harun (Penerbit Universiti Kebangsaan Malaysia, 2002)
This study examines whether organizational factors (such as top management support, training and education of users, existence of steering committees and organization size) influence the performance of accounting information system. Since accounting information system is the biggest component of the information system in the organization, therefore the system is the precedence. Out of 120 manufacturing companies in Bandar Baru Bangi and Shah Alam, which have the accounting information systems that are selected as a sample, only 53 of them gave response to the questionnaire. The result of the empirical study suggested that there are significant positive association between the performance of accounting information systems and organizational factors such as top management support, and training and education of the users. However, even though past research showed a positive relationship between organizational factors such as existence of steering committees and organization size, this study found no such relationship. This is possibly due to usage of accounting software as a computerized accounting information system